MOR/ERK signalling pathway promotes the malignant progression of residual hepatocellular carcinoma cells after insufficient radiofrequency ablation - Yin, Qianxi; Li, Fengjuan; Gao, Feiyan; He, Xiaoying; Liu, Ying; Liu, Yang; Liu, Jiwei; Liu, Shujun; Jia, Guoqun; Ma, Libing (Journal of Contemporary Medical Sciences, 2025)
Objective: Radiofrequency ablation (RFA) is the first-line of treatment for unresectable early hepatocellular carcinoma (HCC). However, the accelerated malignancy progression of residual HCC cells post-RFA pose a major obstacle to its clinical application. The mechanisms underlying the increased malignancy of residual HCC cells following RFA require further investigation. Methods: In the present study, HepG2 cells, an established human HCC cell line, were subjected to repeated heat treatment to simulate residual HCC cells after RFA, surviving cells were designated as HepG2-H cells. Malignancy parameters and μ-opioid receptor (MOR) expression levels were compared between HepG2 and HepG2-H cells. RNA sequencing was subsequently performed to identify differentially expressed genes (DEGs) between the two groups of cells, and pathways enrichment analysis was conducted to investigate signaling pathways potentially driving HepG2-H cells malignancy. Results: HepG2-H cells exhibited significantly elevated malignancy compared to HepG2 cells, as evidenced by enhanced proliferation, migration, and colony formation. MOR expression was significantly upregulated in HepG2-H cells. RNA sequencing revealed that DEGs between the two groups were predominantly enriched in cancer pathways. Furthermore, phosphorylated ERK1/2 (P-ERK1/2) levels were 1.18-fold higher in HepG2-H cells, and the inhibition of MOR activity could reduce both the level of P-ERK1/2 and the malignancy of HepG2-H cells. Conclusion: Our findings suggest that the activation of MOR/ERK signaling pathway contributes to the malignant progression of residual HCC cells post-RFA. Targeting MOR may offer a novel therapeutic strategy to mitigate tumor recurrence following RFA.